2010
DOI: 10.1159/000299063
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Genome Sequencing of a Novel Coliphage Isolated from Engineered <i>Escherichia coli</i>

Abstract: Objectives: To characterize morphological, physicochemical and genomic features of a novel virulent coliphage which was isolated from an engineered Escherichia coli culture and termed engineered E. coli phage (EEP). Methods and Results: Electron microscopy revealed that EEP has an icosahedral head (62 nm in diameter) and a long, flexible tail (138 nm in length). EEP was able to infect all 10 engineered E. coli strains kept in our laboratory, showing a strong ability to lyse engineered E. coli. Sequencing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
27
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 70 publications
8
27
1
Order By: Relevance
“…In addition, Lee et al (2013) evaluated viability in LB broth, and, although coliphage ECP4 showed heat resistance at temperatures below 65°C, ECP4 was reduced by 6-log 10 PFU ml −1 after 10 min, and was not detected after 20 min at 70°C. Similar results were obtained by Li and coworkers at 63 and 72°C (Li et al, 2010). Moreover, several authors have found high resistance at 63°C and moderate resistance at 72°C for lactic acid bacteria (LAB) phages (Mercanti, Guglielmotti, Patrignani, Reinheimer, & Quiberoni, 2012;Pujato et al, 2014).…”
Section: Influence Of Thermal Treatments On Viability and Activity Ofsupporting
confidence: 85%
See 4 more Smart Citations
“…In addition, Lee et al (2013) evaluated viability in LB broth, and, although coliphage ECP4 showed heat resistance at temperatures below 65°C, ECP4 was reduced by 6-log 10 PFU ml −1 after 10 min, and was not detected after 20 min at 70°C. Similar results were obtained by Li and coworkers at 63 and 72°C (Li et al, 2010). Moreover, several authors have found high resistance at 63°C and moderate resistance at 72°C for lactic acid bacteria (LAB) phages (Mercanti, Guglielmotti, Patrignani, Reinheimer, & Quiberoni, 2012;Pujato et al, 2014).…”
Section: Influence Of Thermal Treatments On Viability and Activity Ofsupporting
confidence: 85%
“…refrigeration -4°C-and abusive -50°C-temperatures) and remain biologically active (Coffey et al, 2011) either at refrigeration temperatures or when the cold chain is lost. On the contrary, other authors found that all phage activity was destroyed after 10 min at 60°C (Li et al, 2010). The slightly reduced activity observed in this work at 50°C may be due to disorganization and/or partial denaturation of phage receptors on the bacterial cell surface, thus hindering phage multiplication.…”
Section: Influence Of Thermal Treatments On Viability and Activity Ofcontrasting
confidence: 75%
See 3 more Smart Citations